Cognitive absorption and trust for workplace collaboration in virtual worlds : an information processing decision making perspective - Chandra, Shalini (2014)
Virtual worlds (VWs) are media-rich cognitively engaging technologies that geographically dispersed organizations can use as a cost effective workplace collaboration tool. Using an information processing decision making perspective and building on unique characteristics of VWs, this paper proposes a nomological net for adaptive use intention (AUI) of VWs for workplace collaborations. AUI implies intention to use a technology in a setting different from the one for which it was initially designed. We study the AUI of VWs as a workplace collaboration tool which were originally conceived as recreational gaming platforms. Decision-making literature directs us to reduction of perceived cognitive burden and minimization of risk as the two key motivations for VWs’ AUI. Building on these motivations, the paper identifies cognitive absorption and user trust in VWs as the mechanisms leading to individual-level AUI decision. Drawing on social cognitive theory and literature on trust, the proposed model not only re-specifies the concept of cognitive absorption in the context of VWs but also relates it to the level of trust and usage intention for VWs. We empirically tested the proposed model via data collected from 197 VW users in Singapore. Results demonstrate the significant roles that cognitive absorption’ and user trust play in VW’s usage as a collaboration tool. Further, through a series of post-hoc analyses, we demonstrate the imperative need for considering both cognitive absorption and user trust together in the proposed research model for theoretical parsimony. We also discuss implications for research and practice emerging out of this study.